2017
DOI: 10.1103/physrevd.95.064011
|View full text |Cite
|
Sign up to set email alerts
|

Generalized multi-Galileons, covariantized new terms, and the no-go theorem for nonsingular cosmologies

Abstract: It has been pointed out that non-singular cosmological solutions in second-order scalar-tensor theories generically suffer from gradient instabilities. We extend this no-go result to second-order gravitational theories with an arbitrary number of interacting scalar fields. Our proof follows directly from the action of generalized multi-Galileons, and thus is different from and complementary to that based on the effective field theory approach. Several new terms for generalized multi-Galileons on a flat backgro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 113 publications
5
69
0
Order By: Relevance
“…Based on the effective field theory (EFT) of nonsingular cosmologies [8][9][10], this No-go result has been more clearly illustrated. It is found that the stable nonsingular cosmological models can be implemented only in the theories beyond cubic Galileon, (see also [11,12]). …”
Section: Introductionmentioning
confidence: 99%
“…Based on the effective field theory (EFT) of nonsingular cosmologies [8][9][10], this No-go result has been more clearly illustrated. It is found that the stable nonsingular cosmological models can be implemented only in the theories beyond cubic Galileon, (see also [11,12]). …”
Section: Introductionmentioning
confidence: 99%
“…However, one has to be slightly careful with certain limits. For example, taking the UV limit of action (45) yields…”
Section: F More Comments On Stabilitymentioning
confidence: 99%
“…As was first found in [20] (see also [21]), the R (3) δg 00 operator plays a crucial role in solving the gradient instability problem induced by c 2 s < 0, (see also [30] for the unitarity problem), which suffered by the nonsingular cosmologies based on the Horndeski theory [23] [24][31] [32].…”
Section: Higher Order Derivative Coupling To Gravitymentioning
confidence: 99%